2008
DOI: 10.1161/strokeaha.107.492363
|View full text |Cite
|
Sign up to set email alerts
|

A Very Early Rehabilitation Trial for Stroke (AVERT)

Abstract: Background and Purpose-Very early rehabilitation, with an emphasis on mobilization, may contribute to improved outcomes after stroke. We hypothesized that a very early rehabilitation protocol would be safe and feasible. Methods-We performed a randomized, controlled trial with blinded outcome assessment. Patients at Ͻ24 hours after stroke were recruited from 2 Melbourne metropolitan stroke units. Patients were randomly assigned to receive standard care (SC) or SC plus very early mobilization (VEM) until dischar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
279
2
25

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 339 publications
(330 citation statements)
references
References 25 publications
13
279
2
25
Order By: Relevance
“…A number of authors propose indications and recommend early start of the rehabilitation process (between 24 and 48 hours after the accident) to prevent and minimize the risk of extracerebral complications and promote functional recovery [1][2][3][4]. It is believed that the aggressive detection and treatment of secondary complications, including inactivity related complications, contribute to benefits and that the majority of complications during the acute period may be avoided through early inclusion of physical therapy [5].…”
Section: Introductionmentioning
confidence: 99%
“…A number of authors propose indications and recommend early start of the rehabilitation process (between 24 and 48 hours after the accident) to prevent and minimize the risk of extracerebral complications and promote functional recovery [1][2][3][4]. It is believed that the aggressive detection and treatment of secondary complications, including inactivity related complications, contribute to benefits and that the majority of complications during the acute period may be avoided through early inclusion of physical therapy [5].…”
Section: Introductionmentioning
confidence: 99%
“…In humans, using high-intensity constraint induced movement therapy (CIMT, 3 hours of training based on shaping principles plus immobilizing the intact limb for 90% of the waking hours for 10 days) starting around 10 days after stroke results in adverse outcomes as compared with standard occupational therapy and standard CIMT (two hours of shaping plus 6 hours of immobilization per day Dromerick et al 2009). In contrast, Bernhardt and coworkers suggested that early -within 24 hours -mobilization, i.e., getting the patient out of bed, improves the outcome three months after the stroke (Bernhardt et al 2008). This finding awaits confirmation in a larger sample.…”
Section: Therapeutic Principles Timingmentioning
confidence: 97%
“…В настоящее время идет крупное рандомизиро-ванное контролируемое исследование AVERT, по-священное оценке эффективности и экономиче-ской целесообразности ранней мобилизации паци-ентов после инсульта [2]. Мобилизация начинается в течение 24 ч от начала инсульта и продолжается каждый день первые 14 дней или до момента выпи-ски.…”
Section: аппаратная вертикализацияunclassified